Automated diagnostic system of pathological states of the circulatory system - Книшов, Генадій Васильович; Настенко, Євген Арнольдович; Носовець, Олена Костянтинівна; Береговий, Олександр Анатолієвич; Шаповалова, Валентина Вікторівна; Плахтій, Артур Миколайович (Eastern-European Journal of Enterprise Technologies, 2014)
The results of developing an automated system of diagnosing pathological conditions of a human blood circulatory system have been presented. The system is based on the results of researching functional bonds between arterial blood pressure measurements and cardiac rate frequency in health and disease. Nomographic charts and percentage diagrams, reflecting the type of relation depending on a blood circulatory condition, have been used. The system development has been carried out by means of the PHP programming language and implemented as a web-site. The option of inputting results of multiple arterial blood pressure measurements for analysis allows not only estimating current blood circulation conditions, but also studying the dynamics of changes, happening to an organism under various factors (psychophysical work load, different measures aimed at eliminating pathological conditions and so on). The system provides a great range of modes: passive control (passive monitoring) of a condition domiciliary; efficiency control of measures aimed at eliminating pathological blood circulatory system conditions (surgical treatments and prescribing medicine); assessment of adaptive reserves of sportsmen; control over intraaortic balloon pump (IABP). The results of testing the system operation in different variants of its applying to clinical data have been presented